Four-step enzyme-linked immunosorbent assay for detection of Treponema pallidum antibody. - Farshy, C E (1985)
Further studies of a four-step enzyme-linked immunosorbent assay procedure to detect Treponema pallidum antibody are described. High-titered antibody, produced in rabbits by intravenous injection of T. pallidum, was used to coat polyvinyl chloride microtiter plates. To these plates a known concentration of T. pallidum was added, followed in successive steps by serial dilutions of human sera and appropriately diluted peroxidase-labeled anti-human immunoglobulin G antibody. O-Phenylenediamine was the substrate. A total of 340 sera were obtained from the DeKalb County Sexually Transmitted Diseases Clinic, Atlanta, Ga., and examined within 3 days of receipt. Ninety-six percent test agreement between the enzyme-linked immunosorbent assay and the fluorescent treponemal antibody absorption-double staining test was obtained. A total of 372 additional sera stored at -20 degrees C were examined. The overall sensitivity of the enzyme-linked immunosorbent assay with sera from patients with various stages of syphilis was 96%. With sera from uninfected individuals, the specificity of the enzyme-linked immunosorbent assay was 95%. No antigen instability was noted with the two antigen preparations used during this evaluation.